2007
DOI: 10.1111/j.1539-6924.2007.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Model-Averaged BMDLs: A Study of Model Averaging in Dichotomous Response Risk Estimation

Abstract: Model averaging (MA) has been proposed as a method of accounting for model uncertainty in benchmark dose (BMD) estimation. The technique has been used to average BMD dose estimates derived from dichotomous dose-response experiments, microbial dose-response experiments, as well as observational epidemiological studies. While MA is a promising tool for the risk assessor, a previous study suggested that the simple strategy of averaging individual models' BMD lower limits did not yield interval estimators that met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(149 citation statements)
references
References 24 publications
2
144
0
Order By: Relevance
“…By combining estimates from multiple models, MA gives researchers and regulators alike a method that accounts for statistical variability as well as model uncertainty. This method has been shown by Wheeler and Bailer (2007) to yield point estimates with minimal bias and confidence limits with nominal coverage properties, while producing estimates that are superior to picking one single model. This is true even if this model describes the data "better" than the other models used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By combining estimates from multiple models, MA gives researchers and regulators alike a method that accounts for statistical variability as well as model uncertainty. This method has been shown by Wheeler and Bailer (2007) to yield point estimates with minimal bias and confidence limits with nominal coverage properties, while producing estimates that are superior to picking one single model. This is true even if this model describes the data "better" than the other models used.…”
Section: Discussionmentioning
confidence: 99%
“…In the situations when the two methods do not give identical parameter estimates, a difference in initial estimates along with the existence of local maxima, within the likelihood of the given model being fit, is usually the cause. A small simulation study by Wheeler and Bailer (2007) showed that there was no clear advantage between either the BMDS software and the MADr-BMD optimization strategy. In most all cases, the software converged to the same value, and when the two failed to achieve the same results, the larger likelihood value was found approximately half the time in the US EPA's software, and half the time in the MADr-BMD package.…”
Section: Software Comparisonmentioning
confidence: 99%
See 3 more Smart Citations